1997
DOI: 10.1029/97ja00772
|View full text |Cite
|
Sign up to set email alerts
|

MHD drift ballooning instability near the inner edge of the near‐Earth plasma sheet and its application to substorm onset

Abstract: Abstract. The MHD drift ballooning mode (DBM) instability near the inner edge of the near-Earth plasma sheet is studied by using both the one-fluid generalized progressing wave expansion method and the two-fluid approach. It is found that in the frame of reference •t rest relative to the bulk plasma the DBM may become a purely growing mode in two distinct circumstances, which, for convenience, are called the DBM1 and DBM2, respectively. The/• threshold for the DBM1 is identical with that derived by Ohtani and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 30 publications
2
79
0
Order By: Relevance
“…Therefore one should expect that for satellite off the neutral sheet the B y component from in-situ observation best manifested the Alfvénic nature of the ballooning mode and its interaction with the local current sheet. Furthermore, owing to its Alfvénic nature the ballooning mode may drive FACs (Pu et al, 1997) that possibly related to the very initial brightening and structuring of the breakup arc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore one should expect that for satellite off the neutral sheet the B y component from in-situ observation best manifested the Alfvénic nature of the ballooning mode and its interaction with the local current sheet. Furthermore, owing to its Alfvénic nature the ballooning mode may drive FACs (Pu et al, 1997) that possibly related to the very initial brightening and structuring of the breakup arc.…”
Section: Discussionmentioning
confidence: 99%
“…The electric/magnetic field oscillations with period 45-65 s observed during the most active period of a substorm EP are interpreted as standing Alfvénic modes trapped in an equatorial current layer (Holter et al, 1995). On the other hand, one specific type of Pi2 waves at ∼60 s period emerging 1-3 min prior to the EP onset was suggested by Saito et al (2008b) as a manifestation of ballooning mode which was dubbed by many as the candidate instability leading to substorm EP onset (Pu et al, 1997;Erickson et al, 2000;Cheng, 2004). The other major classes of the onset-related instability, the crossfield current instabilities (CCIs) are kinetic in nature and characterized with frequency range between the ion gyrofrequency and the lower hybrid frequency; therefore in a typical thin current sheet configuration the CCI wave band is largely above the Pi1 range.…”
Section: Introductionmentioning
confidence: 99%
“…A similar scenario emphasizing the role of the high beta on closed field lines has also been suggested for solar flares [Shibasaki, 2003]. The stability of 2D (x, z) magnetotail in a high beta plasma has been examined both theoretically and numerically by various authors studying the ballooning instability [e.g., Miura et al, 1989;Lee and Wolf, 1992;Hurricane, 1997;Pu et al, 1997;Bhattacharjee et al, 1998;Cheng and Lui, 1998;Horton et al, 2001;Zhu et al, 2007;Pritchett and Coroniti, 2010;Raeder et al, 2010] and also the tearing instability [Sitnov and Schindler, 2010]. Collisionless plasmas in inhomogeneous magnetic fields are subject to various kinetic effects such as bounce motion of particles.…”
Section: Introductionmentioning
confidence: 99%
“…A correction of this error leads to a much increased likelihood of ballooning instability occurrence in a realistic plasma sheet. Two-fluid MHD simulations by Pu et al (1997) showed two unstable drift-ballooning mode (DBM) solutions, namely DBM1 (conventional ballooning mode) and DBM2 (Alfvénic ballooning mode), of which the latter is more easily excited in the late substorm growth phase. Using GEOS 2 observations they found that the necessary conditions for DBM2 were fulfilled in 14 out of 16 events.…”
Section: Introductionmentioning
confidence: 99%